Gravitational waves from neutron star excitations in a binary inspiral - Parisi, Alessandro [UNESP]; Sturani, Riccardo (American Physical Society (APS), 2018)
In the context of a binary inspiral of mixed neutron star-black hole systems, we investigate the excitation of the neutron star oscillation modes by the orbital motion. We study generic eccentric orbits and show that tidal interaction can excite the f-mode oscillations of the star by computing the amount of energy and angular momentum deposited into the star by the orbital motion tidal forces via closed form analytic expressions. We study the f-mode oscillations of cold neutron stars using recent microscopic nuclear equations of state, and we compute their imprint into the emitted gravitational waves.